2021
DOI: 10.1155/2021/6695311
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compound Analysis and Pharmacological Screening of Vitex agnus-castus Functional Parts

Abstract: Vitex agnus-castus is a medicinal plant of the Verbenaceae family, widely used in traditional medicine. This study is aimed at investigating the functional variability of phenolic compounds in different parts (leaves, stems, flowers, roots, and seeds) of Vitex agnus-castus methanolic extracts and at assessing their in vitro antidiabetic, antioxidant, and antibacterial activities. The results of HPLC-DAD-QTOF-MS indicated the presence of 25 phenolic compounds with a remarkable variability between plant parts; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Furthermore, steroids, flavonoids, phenolic acids, aldehydes, alcohols, esters, and phytol compounds were reported to have significant antiviral and antimicrobial activities [ 36 ]. In agreement with our results, a previous study showed that the extracts of V. agnus castus fruits and stems had more than 25 phenolic compounds with higher antioxidant activity such as luteolin, 3,4-dihydroxybenzoic acid, vanillic acid, chlorogenic acid, hesperidin [ 37 ]. In contrast to our findings, a previous study conducted the GC/MS analysis of V. agnus castus leaf extracts and revealed the existence of different chemical compositions included, 4,5-Dichloro-1,3-dioxolan-2-one, 1H-Indene, 2,3-dihydro-1,1,2,3,3-pentamethyl, and Isobutyl 4-hydroxybenzoate [ 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, steroids, flavonoids, phenolic acids, aldehydes, alcohols, esters, and phytol compounds were reported to have significant antiviral and antimicrobial activities [ 36 ]. In agreement with our results, a previous study showed that the extracts of V. agnus castus fruits and stems had more than 25 phenolic compounds with higher antioxidant activity such as luteolin, 3,4-dihydroxybenzoic acid, vanillic acid, chlorogenic acid, hesperidin [ 37 ]. In contrast to our findings, a previous study conducted the GC/MS analysis of V. agnus castus leaf extracts and revealed the existence of different chemical compositions included, 4,5-Dichloro-1,3-dioxolan-2-one, 1H-Indene, 2,3-dihydro-1,1,2,3,3-pentamethyl, and Isobutyl 4-hydroxybenzoate [ 38 ].…”
Section: Resultssupporting
confidence: 93%
“…found high total phenolic content in the leaf of V. angus‐cactus leaves. In addition, Berrani et al [44] . found that this plant was a promising source of antidiabetic bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Balpınar et al [43] found high total phenolic content in the leaf of V. anguscactus leaves. In addition, Berrani et al [44] found that this plant was a promising source of antidiabetic bioactive compounds. The previous studies relaved that the pharmaceutical, biological, antimicrobial, antioxidant, and antimutagenic activity of V. agnuscastus seeds caused its' use in the fields of phytomedicine and agriculture.…”
Section: Antioxidant Properties Of Vitex Agnus-castus L Seedmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used as a medicinal plant, and its fruits have traditionally been used in Iran, Italy, Greece, and Egypt to treat gynecological disorders for over 2500 years. [ 12 ] Furthermore, Vitex agnus-castus L. Contains numerous bioactive metabolites (flavonoids, ketosteroids, iridoids, essential oils, etc.) with high reducing features and great activity in the green synthesis of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%